Community journalism and civic engagement in Egypt: the case study of Sahafet Welad El-Balad project - Tawfik, Rasha Saad (AUC Knowledge Fountain, 2015)
While Egypt enjoyed a heritage of local community press, genuine professional endeavors were nearly non-existent till recently. However, with Egypt undergoing a transitional phase, the emergence of community journalism became central to facilitate the shift into a more democratic state. Hence, this study explores the relation between community journalism and civic engagement in Egypt through examining a case study, El-Fayoumeya newspaper published as part of Sahafet Welad El-Balad media project. The study also discusses the state of community journalism in Egypt and the government's media policies related to the issue. This includes an assessment of the state of community journalism in Egypt's governorates, taking into account the challenges it faces and opportunities ahead. Moreover, the study examines the effect of political and socioeconomic status on civic engagement in Egyptian local governorates in post 2011 Revolution, and verifies whether the state of community journalism in Egypt's governorates matches with the definitions of the concept found in the literature. The study utilizes a mix of qualitative and quantitative methods through combining interview data and survey data. It concludes that the poor heritage of community journalism is mainly an outcome of the constraining media policies adopted by the consecutive Egyptian governments to ensure tightening its control over privately-owned newspapers. Also, of the three broad categories of civic engagement (Awareness, Interaction and Participation), awareness is the most evident outcome of recent community journalism initiatives in Egyptian governorates.